(untitled) (ModaPalavra e-periódico, 2021)
The ostomy can be understood as a surgery that aims to produce a new path for the exit of feces or urine from the human body. By empirical observation, it is believed that people with ostomy are unattended by the Textile and Apparel Industry. In this sense, this article aims to present the preliminary structure of a booklet for the development of garments for ostomized people. As data collection instruments, a bibliographic survey and a scripted and semi-structured questionnaire with 12 questions divided into two blocks were used: the individual and his stoma and the ostomized individual and their relationship with clothing. Methodologically, this article can be understood as applied, qualitative, descriptive and field research. The results obtained in the research were converted into recommendations and presented in leaflet format.